2013
DOI: 10.1016/j.ijrobp.2012.11.042
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 3 Trial of Whole Brain Radiation Therapy and Stereotactic Radiosurgery Alone Versus WBRT and SRS With Temozolomide or Erlotinib for Non-Small Cell Lung Cancer and 1 to 3 Brain Metastases: Radiation Therapy Oncology Group 0320

Abstract: Background A phase 3 Radiation Therapy Oncology Group (RTOG) study subset analysis demonstrated improved overall survival (OS) with the addition of stereotactic radiosurgery (SRS) to whole brain radiation therapy (WBRT) in non-small cell lung cancer (NSCLC) patients with 1 to 3 brain metastases. Because temozolomide (TMZ) and erlotinib (ETN) cross the bloodbrain barrier and have documented activity in NSCLC, a phase 3 study was designed to test whether these drugs would improve the OS associated with WBRT + SR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
199
2
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 246 publications
(202 citation statements)
references
References 14 publications
0
199
2
1
Order By: Relevance
“…73,74 A phase II study from China has reported that the combination of WBRT and erlotinib has tolerable toxicities, and suggested a prolonged PFS and OS (class IIb). 75 Conversely, phase II (class IIa and b) 76,77 and phase III (class I) 78 trials in patients with NSCLC brain metastases not enriched for EGFR mutations failed to demonstrate a superiority of the combination of erlotinib with either SRS or WBRT over radiotherapy alone, with a suggestion of worse outcome in patients receiving the combined therapy. A Chinese phase II trial of WBRT with concurrent icotinib, another EGFR inhibitor, has suggested that the combination could improve survival compared with historical controls.…”
Section: Brain Metastases From Nsclcmentioning
confidence: 99%
“…73,74 A phase II study from China has reported that the combination of WBRT and erlotinib has tolerable toxicities, and suggested a prolonged PFS and OS (class IIb). 75 Conversely, phase II (class IIa and b) 76,77 and phase III (class I) 78 trials in patients with NSCLC brain metastases not enriched for EGFR mutations failed to demonstrate a superiority of the combination of erlotinib with either SRS or WBRT over radiotherapy alone, with a suggestion of worse outcome in patients receiving the combined therapy. A Chinese phase II trial of WBRT with concurrent icotinib, another EGFR inhibitor, has suggested that the combination could improve survival compared with historical controls.…”
Section: Brain Metastases From Nsclcmentioning
confidence: 99%
“…However, individually, only one out of 7 randomized controlled trials RCTs included in this meta-analysis showed a some survival improvement following the addition of temozolomide to radiotherapy, with median survival times of 7and 8.6 months in the RT arm and TMZ plus RT arm, respectively (15). In four randomized controlled trials that compare radiotherapy to concomitant TMZ and RT, the OS was lower in patients who were treated with combination TMZ and RT (11,(19)(20)(21) It is hard to compare the results of our study, that was performed on a homogenous group of patients ;with the previously mentioned studies which included more heterogeneous groups of patients and with different treatment regimens.…”
Section: Discussion:-mentioning
confidence: 91%
“…All plans used A 6 MV flattening filter free beam with the maximum repetition rate of 1400 MU/min and were calculated with 2° CP increment and a 2 mm isotropic dose grid resolution. The prescriptions followed RTOG 0320 protocol,24 depending on the target size: 24 Gy to the planning target volume (PTV) <2 cm, 18 Gy to the PTV between 2.1–3 cm, and 15 Gy to the 3.1–4 cm PTV. Plans 4‐6 also employed common OAR objectives from the same protocol.…”
Section: Methodsmentioning
confidence: 99%